ALCOHOL ADDICTION IN THE SYSTEM OF FORMS OF DEVIANT BEHAVIOR OF MINORS - J., Schramm H.; A., Zhetpisbayev B.; A, Tynybekov S. (Farabi Journal of Social Sciences, 2019)
Abstract. Solving the problem of combating alcohol abuse of minors seems to be the most effective only by studying the patterns of genesis and the further development of the mechanism of addiction and addictive forms of behavior, one of which is the alcoholization of minors. The analysis of addiction and addictive forms of behavior makes it possible to understand their real place in the structure of public relations, to predict the consequences of their distribution and to take measures to eliminate these negative phenomena. Antisocial behavior of a minor in the form of alcoholism is interconnected by the influence of various factors, primarily the external social environment (especially the microenvironment), as well as the individual characteristics of the minor’s personality, which cause his individual response to various life problems, independent solving which is problematic for a minor. The article analyzes the emergence and development of alcohol addiction among minors, and also the authors conducted sociological survey to identify different forms of addiction among schoolchildren and students in Kazakhstan. This scientific article is based on traditional and innovative approaches, and such methods as the dialectical method of cognition, comparison, analysis and other empirical methods are widely used.